Rice Production Estimation In Central Sulawesi Through The Utilization Of Rainfall By Using Generalized Additive Model - Handayani, L; Amelia, R; Putera, F H A (Program Studi Matematika, Universitas Tadulako, 2019)
Climate models that are able to simulate rainfall in Indonesia so far have not been found. The highly complex topography and interaction of the sea, land and atmosphere adds to the complexity of simulations and predictions of rainfall in Indonesia, particularly in Central Sulawesi. This research focuses on utilizing the results of prediction or forecast rainfall. Rainfall forecasting results obtained are then modeled with data on the level of rice production, so we can predict the future supply of rice (rice). This study examines statistical downscaling modeling with a generalized additive model approach to describe the rainfall events that occur within a certain time period. The data used is rainfall data in Central Sulawesi Province, because this region is a supplier of rice in Sulawesi.